Bioinspired self-shaping clay composites for sustainable development - Zhang, Yuxiang (2022)
Bioinspired self-shaping is an approach used to transform flat materials into unusual three-dimensional (3D) shapes by tailoring the internal architecture of the flat material. Bioinspiration and bioinspired materials have a high potential for fostering sustainable development, yet are often fashioned out of expensive and synthetic materials. In this work, we use bioinspiration to endow clay with self-shaping properties upon drying. The composites created are based on clay and starch, and the internal architecture is built using celery fibers. The viscosity, shrinkage, and bending of the architected composite monolayers are studied for several compositions by measuring penetration depth and using optical characterization methods. Bilayer structures inspired from plants are then processed using a simple hand layup process to achieve bending, twisting, and combinations of those after drying. By layering a mixture of 32 vol% clay, 25.8 vol% starch, and 42.2 vol% water with 40 wt% embedded aligned celery fibers, it is possible to obtain the desired shape change. The work presented here aims at providing a simple method for teaching the concept of bioinspiration, and for creating new materials using only clay and plant-based ingredients. Rejuvenating clay with endowed self-shaping properties could further expand its use. Furthermore, the materials, methods, and principles presented here are affordable, simple, largely applicable, and could be used for sustainable development in the domain of education as well as materials and structures.